Orange Spiny Whitefly, Aleurocanthus spiniferus Quaintance (Insecta: Hemiptera: Aleyrodidae) - Jamba Gyeltshen; Amanda Hodges; Greg S. Hodges (EDIS)
Orange spiny whitefly, Aleurocanthus spiniferus Quaintance, is a native pest of citrus in tropical Asia. In the early 1920s, pest outbreak infestation levels caused Japan to begin a biological control program. Primarily, orange spiny whitefly affects host plants by sucking the sap but it also causes indirect damage by producing honeydew and subsequently promoting the growth of sooty mold. Sooty mold is a black fungus that grows on honeydew. Heavy infestations of orange spiny whitefly, or other honeydew-producing insects such as scales, mealybugs, aphids, and other whitefly species, can cause sooty mold to completely cover the leaf surface and negatively affect photosynthesis. This document is EENY-341, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2005.